Bahasa Indonesia sebagai Pilar Identitas Akademik : Revitalisasi Sikap dan Etika Berbahasa Mahasiswa di Era Digital - Veronika Erlina Deso; Maria Roslinda; Maria Martika; Rais Nurmala Hasan; Salsabilah Ayu Fernanda; Yeremias Bardi (Lembaga Pengembangan Kinerja Dosen, 2026)
This study examines Indonesian as a pillar of academic identity and the urgency of revitalizing students' language attitudes and ethics in the digital era. The rapid development of digital communication has influenced students' language practices in academic contexts, which tend to lead to the use of informal, impolite language that does not reflect academic ethics. This study aims to describe students' language attitudes, academic communication patterns, and the level of awareness of language ethics in the use of Indonesian in higher education. This study used a qualitative approach with participatory observation techniques and in-depth interviews with students. The results show that students basically have normative knowledge of good and correct Indonesian, but this knowledge has not been consistently internalized in academic communication practices, especially in the digital space. The dominant digital communication culture has weakened students' sensitivity to politeness, ethics, and language professionalism. Furthermore, Indonesian language learning in higher education is still more oriented towards the technical aspects of writing than the formation of academic attitudes and identities. The implications of this study emphasize the importance of revitalizing Indonesian language learning that is contextual, reflective, and oriented towards strengthening students' attitudes, ethics, and academic identities in the digital era.